Persepsi Pendengar Kelas Agama Terhadap Pengajian Agama di Masjid-Masjid Daerah Hulu Langat - Abdul Kadir, Fakhrul Adabi (Jurnal Usuluddin, 2009)
The role of a mosque from the beginning until to this day as a learning centre has been acknowledged. Hence almost every mosque in Malaysia has programs for religious classes as their main activity for the formation of a knowledge society and individuals. This research focuses on community perceptions of religious classes conducted in the mosques of the district of Hulu Langat, Selangor Darul Ehsan. The perceptions required in this research were about the tutors of religious classes, teaching contents, teaching techniques and class schedules at the mosques. In collecting datas, the research used the method of literarture review and field research methods including questionnaires, interviews and observation.